Yorkshire Lyrics : Poems written in the Dialect as Spoken in the West Riding of Yorkshire. To which are added a Selection of Fugitive Verses not in the Dialect - Hartley, John, 1839-1915 (Salt Lake City, UT : Project Gutenberg, 2006)
"Yorkshire Lyrics" by John Hartley is a collection of poems written in the late 19th century, showcasing the dialect of the West Riding of Yorkshire. The verses celebrate the everyday life, morals, and emotions of Yorkshire folk, often with a humorous or reflective twist. Hartley's work encapsulates local culture and the charm of rural existence, likely featuring characters drawn from the author's experiences and observations. The opening portion introduces readers to the lyrical style of the poet, establishing the thematic focus on the beauty of simple, yet profound, moments in life. In the poem "Mi Darling Muse," Hartley personifies his muse, expressing a playful relationship with the act of writing. He acknowledges the struggle of finding inspiration but retains a hopeful and joyful spirit about the craft of poetry. Other poems, such as "To a Daisy, Found blooming March 7th," highlight a connection to nature, as well as the fleetingness of beauty and life. This initial glimpse into the collection reveals Hartley$1 (Bs ability to blend humor, local dialect, and poignant reflection, inviting readers to resonate with the universal truths found within Yorkshire life. (This is an automatically generated summary.)s
Release date is 2006-10-05
Produced by Alison Bush
Keywords: Dialect poetry, English -- England -- Yorkshire; Yorkshire (England) -- Poetry